Health-related quality of life and antihypertensive medication adherence among older adults - Holt, Elizabeth Winter (Oxford University Press, 2010)
Purpose: health-related quality of life (HRQOL) is an important psycho-social characteristic which may impact an individual’s ability to manage their chronic disease. We examined the association between HRQOL and antihypertensive medication adherence in older adults. Methods: participants were part of a cohort study of older adults enrolled in a managed care organisation and treated for hypertension (n = 2,180). Physical and Mental Component Summary Scores (PCS and MCS) of HRQOL were assessed using the RAND Medical Outcomes Study 36-item tool. Adherence to antihypertensive medication was assessed with the eight-item Morisky Medication Adherence Scale. Results: the mean age of participants was 75.0 ± 5.6 years, 69.3% were white, 58.5% were women and 14.1% had low antihypertensive medication adherence. Low HRQOL scores were associated with lower levels of antihypertensive medication adherence in older adults. After adjustment for covariates, those with low PCS and MCS scores were 1.33 (95% CI 1.01, 1.74) and 2.26 (95% CI 1.74, 2.97) times more likely, respectively, to have low antihypertensive medication adherence than those with PCS and MCS scores in the top 2 tertiles. Conclusions: low HRQOL may be an important barrier to achieving high medication adherence.